Analisis Desain Kebijakan Mal Pelayanan Publik - Miftah Sayyid Persada; Sidik Pramono (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
The implementation of Public Service Malls (MPP) in Indonesia has experienced rapid growth in number and has succeeded in improving public perceptions of service comfort. However, behind this improvement in perceived satisfaction, the presence of MPPs continues to face fundamental challenges in the form of fragmentation and sectoral ego. This article aims to analyze the policy design of MPPs in order to understand why substantive service integration has not yet been achieved. This study employs a qualitative descriptive method with a literature review approach. The analysis is conducted using the policy design elements framework of Thomas Birkland (2015) and the social construction theory of Anne Schneider and Helen Ingram (1993). The findings reveal fundamental weaknesses in the policy design of MPPs. First, within the causal model, the policy is trapped in the oversimplified assumption that the unification of physical locations (co-location) will automatically result in system integration. Second, there is an imbalance in the treatment of policy targets; the public as beneficiaries (advantaged) are facilitated with infrastructure that enhances satisfaction, while the bureaucracy as contenders receives only symbolic burdens without coercive mechanisms to integrate their business processes. Third, the implementation structure demonstrates an unclear hierarchy between managers and service providers, in which DPMPTSP, as the MPP manager, lacks enforcement power over vertical agencies and other technical departments. This study concludes that MPPs currently exhibit pseudo-integration, improving only the physical appearance (front office) while remaining fragmented in business processes (back office).